A Model of Customer Satisfaction with Service Encounters Involving Failure and Recovery - Smith, Amy K.; Bolton, Ruth N.; Wagner, Janet (Journal of Marketing Research, 1999)
Customers often react strongly to service failures, so it is critical that an organization's recovery efforts be equally strong and effective. In this article, the authors develop a model of customer satisfaction with service failure/recovery encounters based on an exchange framework that integrates concepts from both the consumer satisfaction and social justice literature, using principles of resource exchange, mental accounting, and prospect theory. The research employs a mixed-design experiment, conducted using a survey method, in which customers evaluate various failure/recovery scenarios and complete a questionnaire with respect to an organization they recently had patronized. The authors execute the research in the context of two different service settings, restaurants and hotels. The results show that customers prefer to receive recovery resources that “match” the type of failure they experience in “amounts” that are commensurate with the magnitude of the failure that occurs. The findings contribute to the understanding of theoretical principles that explain customer evaluations of service failure/recovery encounters and provide managers with useful guidelines for establishing the proper “fit” between a service failure and the recovery effort.